2022
DOI: 10.7759/cureus.26691
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Hydroxyurea as Adjuvant Therapy in Pediatric Patients of Transfusion-Dependent Beta-Thalassemia Major at Zhob, Balochistan

Abstract: BackgroundHydroxyurea is being used effectively in sickle cell anemia and thalassemia intermedia. Its role in transfusion-dependent beta-thalassemia major yet needs to be clearly established. This study has been carried out to assess the efficacy and safety of hydroxyurea as adjuvant therapy in pediatric cases of transfusion-dependent beta-thalassemia major disease. Materials and methodsThis quasi-experimental study was carried out at District Headquarter Hospital (DHQ), Zhob, from February 2021 to January 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Sources: References [14,17] Three studies compared the change in HbF between two groups. Pooled meta-analysis showed that the mean HbF was higher in patients receiving hydroxyurea; however, the difference was statistically insignificant (MD: 2.24, 95% CI: -0.53, 5.00), as shown in Figure 4.…”
Section: Figure 3: Forest Plot Showing Effect Of Hydroxyurea On Inter...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sources: References [14,17] Three studies compared the change in HbF between two groups. Pooled meta-analysis showed that the mean HbF was higher in patients receiving hydroxyurea; however, the difference was statistically insignificant (MD: 2.24, 95% CI: -0.53, 5.00), as shown in Figure 4.…”
Section: Figure 3: Forest Plot Showing Effect Of Hydroxyurea On Inter...mentioning
confidence: 99%
“…Sources: References [14,16] High heterogeneity was reported among the study results. Two studies compared ferritin levels.…”
Section: Figure 5: Forest Plot Showing Effect Of Hydroxyurea On Hemog...mentioning
confidence: 99%